Translation of wakamono kotoba in the comic Jujutsu Kaisen by Akutagami Gege - Wicaksono, Thomas Adhi; Hernawati, Heni; Supriatnaningsih, Rina; Prasetiani, Dyah (Universitas Dian Nuswantoro, 2022)
In the field of language, Wakamono Kotoba, the language of young people, often experiences changes significantly over time. These changes are also influenced by the entry of foreign cultures into Indonesia in the Japanese youth association which also influences the mindset and way of socializing among young people. Wakamono Kotoba as a variety of Japanese that is spoken by young people in Japan adds curiosity for further studies. The creation of wakamono kotoba is a form of creativity among young Japanese so that parents and non-Japanese native cannot understand the words in Wakamono Kotoba. The purpose of this research is to provide knowledge to Japanese language learners about Wakamono Kotoba as well as providing information about translation related to Wakamono Kotoba. This research uses qualitative methodology. The result of this study is that there are 75 Wakamono Kotoba data and 7 types of translation methods identified in Jujutsu Kaisen comics vol 1 and 2. From those 75 data, Characteristics of Wakamono Kotoba in terms of word class are found 26 adjectives, 21 verbs, 20 nouns, 5 adverbs, and 3 conjunctions. Furthermore, in terms of Wakamono Kotoba characteristics, researcher found that there were elements of word shortening, changes in sound accompanied by sound lengthening, word reversal, word change, borrowing from a foreign language, special vocabulary and mix in each word class. Of the 7 translation methods, the popular translation method that is the most widely used in this object study is the word-by-word translation method.